Mediation of Endogenous β-Endorphin by Tetrandrine to Lower Plasma Glucose in Streptozotocin-Induced Diabetic Rats. Issue 2 (2004) - Hsu, Jen-Hao; Wu, Yang-Chang; Liou, Shorong-Shii; Liu, I-Min; Huang, Lee-Wen; Cheng, Juei-Tang
Abstract : The role of β-endorphin in the plasma glucose-lowering action of tetrandrine in streptozotocin-induced diabetic rats (STZ-diabetic rats) was investigated. The plasma glucose concentration was assessed by the glucose oxidase method. The enzyme-linked immunosorbent assay was used to determine the plasma level of β-endorphin-like immunoreactivity (BER). The mRNA levels of glucose transporter subtype 4 (GLUT4) in soleus muscle and phosphoenolpyruvate carboxykinase (PEPCK) in the liver of STZ-diabetic rats were detected by Northern blotting analysis. The expressed protein of GLUT4 or PEPCK was characterized by Western blotting analysis. Tetrandrine dose-dependently increased plasma BER in a manner parallel to the decrease of plasma glucose in STZ-diabetic rats. Moreover, the plasma glucose-lowering effect of tetrandrine was inhibited by naloxone and naloxonazine at doses sufficient to block opioid μ-receptors. Further, tetrandrine failed to produce plasma glucose-lowering action in opioid μ-receptor knockout diabetic mice. Bilateral adrenalectomy eliminated the plasma glucose-lowering effect and plasma BER-elevating effect of tetrandrine in STZ-diabetic rats. Both effects were abolished by treatment with hexamethonium or pentolinium at doses sufficient to block nicotinic receptors. Tetrandrine enhanced BER release directly from the isolated adrenal medulla of STZ-diabetic rats and this action was abolished by the blockade of nicotinic receptors. Repeated intravenous administration of tetrandrine (1.0 mg/kg) to STZ-diabetic rats for 3 days resulted in an increase in the mRNA and protein levels of the GLUT4 in soleus muscle, in addition to the lowering of plasma glucose. Similar treatment with tetrandrine reversed the elevated mRNA and protein levels of PEPCK in the liver of STZ-diabetic rats. The obtained results suggest that tetrandrine may induce the activation of nicotinic receptors in adrenal medulla to enhance the secretion of β-endorphin, which could stimulate opioid μ-receptors to increase glucose utilization or/and reduce hepatic gluconeogenesis to lower plasma glucose levels in STZ-diabetic rats.